Kualitas Pelayanan Pembuatan Akta Kelahiran Pada Dinas Kependudukan Dan Pencatatan Sipil Kota Manado - Johanis Adrian Himber; Elfie Mingkid; Antonius Purwanto (Sam Ratulangi University, 2022)
This study aims to identify, examine, and analyze the quality of services for making birth certificates at the Department of Population and Civil Registration of the City of Manado. The research was carried out in March 2022 at the Department of Population and Civil Registration of the City of Manado. The type of research used in this research is descriptive qualitative research, namely research or subject study with the main objective of describing or describing a situation or event. Data collection techniques in this study using observation techniques, interviews and documentation. The sources of information in this study were 6 informants who were selected non-randomly or not randomly using a purposive technique, namely determining the informants to be interviewed on research objects related to the problem or research focus. The data analysis technique used is data reduction, data presentation, data triangulation, drawing conclusions. The results of the research based on data analysis and findings in the field show the quality of service for making birth certificates at the Department of Population and Civil Registration of the City of Manado from the aspects of tangibles, reliability, responsiveness, assurance, empathy is still low and needs to be further improved.